PPP based Indian Highway Infrastructure Plan with Respect to Quality of Highway - Sushma, Kesari; Swaroop, Ajay (International Journal of Psychosocial Rehabilitation, 2020)
Public-private partnerships (PPPs) have turned into a noteworthy worldwide marvel, and governments are using them all the more every now and again to convey ventures that fulfill expanding cultural requests in infrastructure segments, for example, highways. Contrasted with conventional undertaking conveyance drawing near, PPPs are long-haul contracts between the general population and the private areas, where the private part is occupied with more venture errands and acknowledges more dangers. In this paper, assessment of quality in infrastructure will take place.